Endothelial progenitor cells in acute ischemic stroke - Martí‐Fàbregas, Joan; Crespo, Javier; Delgado‐Mederos, Raquel; Martínez‐Ramírez, Sergi; Peña, Esther; Marín, Rebeca; Dinia, Lavinia; Jiménez‐Xarrié, Elena; Fernández‐Arcos, Ana; Pérez‐Pérez, Jesús; Querol, Luis; Suárez‐Calvet, Marc; et al. (Brain and behavior, 2013)
Objectives The levels of circulating endothelial progenitor cells (EPCs) in ischemic stroke have not been studied extensively and reported results are inconsistent. We aimed to investigate the time course, the prognostic relevance, and the variables associated with EPC counts in patients with ischemic stroke at different time points. Material and methods We studied prospectively 146 consecutive patients with ischemic stroke within the first 48 h from the onset of symptoms (baseline). We evaluated demographic data, classical vascular risk factors, treatment with thrombolysis and statins, stroke etiology, National Institute of Health and Stroke Scale score and outcome (favorable when Rankin scale score 0–2). Blood samples were collected at baseline, at day 7 after stroke (n = 121) and at 3 months (n = 92). The EPC were measured by flow cytometry. Results We included 146 patients with a mean age of 70.8 ± 12.2 years. The circulating EPC levels were higher on day 7 than at baseline or at 3 months (P = 0.045). Pretreatment with statins (odds ratio [OR] 3.11, P = 0.008) and stroke etiology (P = 0.032) were predictive of EPC counts in the baseline sample. EPC counts were not associated with stroke severity or functional outcome in all the patients. However, using multivariate analyses, a better functional outcome was found in patients with higher EPC counts in large‐artery atherosclerosis and small‐vessel disease etiologic subtypes. Conclusions After acute ischemic stroke, circulating EPC counts peaked at day 7. Pretreatment with statins increased the levels of EPC. In patients with large‐artery atherosclerosis and small‐vessel disease subtypes, higher counts were related to better outcome at 3 months. After acute ischemic stroke, circulating endothelial progenitor cell (EPC) counts peaked at day 7. Pretreatment with statins increased the levels of EPC. In patients with large‐artery atherosclerosis and small‐vessel disease subtypes, higher counts were related to better outcome at 3 months.